PERSEPSI MASYARAKAT TENTANG MENAFSIRKAN ARAH POLITIK DAN KEBIJAKAN PUBLIK - Siyamsih, Dwi (PT. Anagata Sembagi Education, 2024)
In the context of interpreting political direction, individuals are often concerned with several key factors:Public Policy: The interpretation of political direction is often related to the analysis of public policies proposed, passed or enacted by the government. This includes policies in areas such as the economy, education, health, environment and security.Political Trends: Individuals also pay attention to long-term political trends, including shifts in political ideology, support for specific political parties, and electoral dynamics.Political Leadership: Interpretation of political direction also includes analysis of political leadership, including leadership style, proposed policies and responses to key issues. Social and Economic Context: The social and economic context also plays an important role in the interpretation of political direction. Individuals consider factors such as unemployment rates, economic inequality, changing demographics and social tensions. Community Involvement: People's involvement in the political process, including participation in elections, protests, and social movements, is also a factor considered in the interpretation of political direction. This research is a qualitative approach research with descriptive mode data type, which seeks to present objective facts in accordance with the conditions that occurred at the time the research was conducted. Qualitative descriptive research seeks to describe all existing symptoms or circumstances, namely the state of the symptoms according to what they are at the time the research was conducted. Conclusions about community perceptions of interpretations of political direction and public policy Communities have a variety of views and interpretations of political direction and public policy. Factors such as cultural, social, economic and educational backgrounds can influence the way people see and understand government measures.